The effect of coherent interface on strain-rate sensitivity of highly textured Cu/Ni and Cu/V multilayers. (15th March 2019) - Liu, Y.; Yang, K.M.; Hay, J.; Fu, E.G.; Zhang, X.
Abstract: The strain-rate sensitivity (SRS) depends on the evolution of applied shear stress and dislocation activation volume. Quantifying SRS at different grain sizes is important to understand thermally activated plastic deformation. Here we present SRS studies of highly textured Cu/Ni and Cu/V multilayers with individual layer thickness ( h ) varying from 1 to 100 nm. When h > 10 nm, the SRS of Cu/Ni multilayers increases with decreasing h, but the opposite holds when h < 10 nm due to the formation of coherent interface. In comparison, the SRS of Cu/V multilayers keeps unchanged when h < 10 nm. Our findings provide more insight to understand the size-dependent deformation mechanisms in multilayers. Graphical abstract: The effect of coherent interface on SRS of highly textured Cu/X (X = Ni and V) multilayers with individual layer thickness ( h ) varying from 1 to 100 nm is studied by using a modified nanoindentation test method. When h > 10 nm, the SRS of Cu/Ni multilayers increases with decreasing h, but the opposite holds when h < 10 nm due to the formation of coherent interface. The SRS of Cu/V multilayers keeps almost unchanged when h < 10 nm, this may be ascribed to the existing misfit dislocations at the semi-coherent interface. Unlabelled Image